Odprta vprašanja varstva upnika po 168. členu Zakona o izvršbi in zavarovanju (ZIZ) - Ovčak Kos, Maja (Pravnik, 2016)
The authors discuss some particular questions regarding a claim filed against the defendant under the Article 168(5) of Slovenian Claim Enforcement and Security Act (ZIZ). The research focuses mainly on the main purpose of the sale and the acquisition of the property, with particular reference to actio Pauliana. The authors discuss the issues regarding the correct type of claim to lodge against the defendant, who the defendant/s is/are, and the questions whether the claimant is entitled to bring forward an action under Article 168(5) ZIZ before applying for a warrant to seize property. They further discuss the type of protection the creditor has concerning the matrimonial assets of spouses and what implications the extended legal basis under Article 168(5) ZIZ has, to identifying the correct type of case that needs to be pursued against the defendant.
Keywords: dolgovi; izvršilni postopek; izvšba; nepremičnine; terjatve